Leaching and ion exchange based recovery of nickel and cobalt from a low grade, serpentine-rich sulfide ore using an alkaline glycine lixiviant system. (1st January 2020) - Eksteen, J.J.; Oraby, E.A.; Nguyen, V.
Highlights: Alkaline glycine is used to leach Ni and Co from low grade sulfide ores high in magnesium. Ion exchange resin Purolite S930+ was used to extract the metals from the leachate. High extraction yields were obtained during both the leach and the ion exchange. Although the kinetics is slow, the process holds promise for heap and vat leaching. The direct leach approach allows the treatment of acid consuming Mg and Fe rich Ni-Co ores. Abstract: The paper presents the outcomes of exploratory research relating to the atmospheric pressure and ambient temperature leaching of nickel and cobalt from a Western Australian low grade, disseminated, nickel-cobalt sulfide ore, and the subsequent recovery using ion exchange (IX) using alkaline glycine solutions in mildly oxidizing environments. The results present a foundation for a direct leach approach at ambient conditions, particularly if upstream opportunities are considered (heap leach, in-situ leach, or vat leach, or bulk ore leach) from low grade Ni-Co resources. The results for cobalt are particularly exciting given the low recovery of cobalt in most smelting operations and the loss of cobalt to converter slags in conventional approaches. In addition, significant nickel losses are often incurred to flotation cleaner tailings to make a smeltable concentrate at an acceptable level of magnesium. The study showed that even though glycine-based leach rates for Ni and Co are slow, no passivation was observed and about 83.5% Ni and 76.3% Co were extracted at room temperature using conventional bottle rolls over a 672 h period using a multistage extraction (i.e. leachate decant and reagent refresh with either new reagent or recycled barren raffinate). The ore contained cobalt-bearing pentlandite as the predominant Ni-Co mineralization, with Kaolinite-serpentine group, magnesite and hydrotalcite the predominant oxide and pyrrhotite as the predominant sulfide gangue minerals. The effects of glycine concentration, pH and temperature have been studied. It was found that leaching at pH 10.0 gave significant better leach Ni and Co extraction than operating at higher pH of 11.5. In glycine leach campaigns, the dissolution of iron, magnesium, silicon, manganese and other impurities were insignificant. This is particularly important for iron removal which would normally have posed a significant solid-liquid separation and waste disposal cost and magnesium, given the very high levels of magnesium that would normally have dissolved from such ores in acidic systems. Excellent recovery of Ni and Co from leach solutions was achieved by a selected ion exchange resin (Purolite S930Plus) and high Ni and Co dissolution was achieved using recycle glycine solutions after metals adsorption and pH adjustment.